2015
DOI: 10.1093/eurpub/ckv181
|View full text |Cite
|
Sign up to set email alerts
|

Do different parenting patterns impact the health and physical growth of ‘left-behind’ preschool-aged children? A cross-sectional study in rural China

Abstract: This study highlighted the impact of the characteristics of the primary caregiver on a child's health and development and the importance of practical interventions for preschool-aged children who are left behind and raised with different parenting patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
2
24
0
2
Order By: Relevance
“…Furthermore, our estimates on physical health complement previous studies highlighting the greater risk of health problems among children aged 10–16 years old that is associated with parental migration (Gao et al., ; Li et al., ). Several other studies instead find evidence that particularly younger children (preschool‐ and elementary school‐age children) are more vulnerable to health problems than older children (Lei et al., ; Mo et al., ). Similar to our study, Wanjie et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our estimates on physical health complement previous studies highlighting the greater risk of health problems among children aged 10–16 years old that is associated with parental migration (Gao et al., ; Li et al., ). Several other studies instead find evidence that particularly younger children (preschool‐ and elementary school‐age children) are more vulnerable to health problems than older children (Lei et al., ; Mo et al., ). Similar to our study, Wanjie et al.…”
Section: Resultsmentioning
confidence: 99%
“…This paper lies at the intersection of three strands of literature that link migration and family left-behind. The first strand is the New Economics 1 For examples, see contributions of Creighton et al (2011), Li, Liu, andZang (2015), Mo et al (2016), Zhao and Yu (2016), Lei, Liu, and Hil (2018).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research in this field over the last three decades has yielded conflicting results. Most studies found that leftbehind children were more likely to be stunted, underweight, or wasted compared with other children [3][4][5][6][7][8][9][10][11], but others found that left-behind children performed similarly to, or even better than, non-left-behind children on these anthropometric indicators [12][13][14][15]. In addition, some studies identified a higher risk of anemia among left-behind than non-left-behind children [16,17], but other work found no such difference [14].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research in this field over the last three decades has yielded conflicting results. Most studies found that left-behind children were more likely to be stunted, underweight, or wasted compared with other children [3][4][5][6][7][8][9][10][11], but others found that left-behind children performed similarly to, or even better than, non-left-behind children on these anthropometric indicators [12][13][14][15]. In addition, some studies identified a higher risk of anemia among left-behind than non-left-behind children [16,17], but other work found no such difference [14].…”
Section: Introductionmentioning
confidence: 99%